The commercialization of pharmaceutical patents in China - Hou, James (Asian commercial, financial and economic law and policy series, 2021)
"Presenting detailed analysis of the industrialization and commercialization of pharmaceutical patents in China, this timely book explores a range of related topics including a comparison of the ideal and existing state of the pharmaceutical market and patent industrialization. It argues that the core purpose of the industrialization of pharmaceutical patents is to promote the development of the local pharmaceutical industry whist also protecting society's right to safe and effective medication. Chapters examine the special application issues of patent law in relation to the field of pharmaceuticals, compare the Chinese and American legal systems and their approach to pharmaceutical patents, and provide in depth political and legal analysis of the industry. James Hou suggests methods by which the Chinese legal system can seek to improve its governance of pharmaceutical patents and balance the conflicts of interest arising between new drug developers, established drug manufacturers and the end users. Featuring comprehensive coverage of patents in the Chinese pharmaceutical industry, this book will be a key resource for scholars and students of commercial, pharmaceutical and intellectual property law, whilst also being of interest to industry talents discovering the potential of their own innovations"--